A Comparison of Proposed Biosimilar LA‐EP2006 and Reference Pegfilgrastim for the Prevention of Neutropenia in Patients With Early‐Stage Breast Cancer Receiving Myelosuppressive Adjuvant or Neoadjuvant Chemotherapy: Pegfilgrastim Randomized Oncology (Supportive Care) Trial to Evaluate Comparative Treatment (PROTECT‐2), a Phase III, Randomized, Double‐Blind Trial. (18th April 2016) - Blackwell, Kimberly; Donskih, Roman; Jones, C. Michael; Nixon, Allen; Vidal, Maria J.; Nakov, Roumen; Singh, Pritibha; Schaffar, Gregor; Gascón, Pere; Harbeck, Nadia
Abstract : Background: Pegfilgrastim is widely used for the prevention of chemotherapy‐induced neutropenia. In highly regulated markets, there are currently no approved biosimilars of pegfilgrastim. Pegfilgrastim Randomized Oncology (Supportive Care) Trial to Evaluate Comparative Treatment (PROTECT‐2) was a confirmatory efficacy and safety study designed to compare proposed biosimilar LA‐EP2006 with reference pegfilgrastim (Neulasta, Amgen) in early‐stage breast cancer patients receiving adjuvant or neoadjuvant myelosuppressive chemotherapy. Methods: A total of 308 patients were randomized to LA‐EP2006 or reference pegfilgrastim. Each patient received TAC (intravenous docetaxel 75 mg/m 2, doxorubicin 50 mg/m 2, and cyclophosphamide 500 mg/m 2 ) on day 1 of each cycle, for six or more cycles. Pegfilgrastim (LA‐EP2006 or reference) was given subcutaneously (6 mg in 0.6 mL) on day 2 of each cycle. The primary endpoint was duration of severe neutropenia (DSN) during cycle 1 (number of consecutive days with an absolute neutrophil count <0.5 × 10 9 /L), with equivalence confirmed if 90% and 95% confidence intervals (CIs) were within a 1‐day margin. Results: Baseline characteristics were well balanced. DSN was equivalent between groups at mean ± SD 1.36 ± 1.13 (LA‐EP2006, n = 155) and 1.19 ± 0.98 (reference, n = 153) in cycle 1. With a treatment difference (reference minus LA‐EP2006) of −0.16 days (90% CI −0.36 to 0.04; 95% CI −0.40 to 0.08), LA‐EP2006 was equivalent to reference pegfilgrastim. Secondary efficacy parameters were similar between groups during cycle 1 and across cycles. Safety profiles were also similar between groups. No neutralizing antibodies against pegfilgrastim, filgrastim, or polyethylene glycol were detected. Conclusion: LA‐EP2006 and reference pegfilgrastim were therapeutically equivalent and comparable regarding efficacy and safety in the prevention of neutropenia in patients with early‐stage breast cancer receiving TAC. Implications for Practice: The granulocyte colony‐stimulating factor pegfilgrastim is widely used for the prevention of chemotherapy‐induced neutropenia. Biosimilars are biologics with similar quality, safety, and efficacy to a reference product that may increase the affordability of treatment compared with their reference compounds. There are currently no approved biosimilars of pegfilgrastim in highly regulated markets. No previous phase III studies have been performed with LA‐EP2006. PROTECT‐2 was conducted to confirm the similarity of the proposed biosimilar LA‐EP2006 to pegfilgrastim. Biosimilar pegfilgrastim (LA‐EP2006) may benefit oncology patients by offering increased access to biological treatments that may improve clinical outcomes. This means that patients could potentially be treated prophylactically with biologics rather than only after complications have occurred. Abstract : PROTECT‐2 compared biosimilar LA‐EP2006 with reference pegfilgrastim for the prevention of chemotherapy‐induced neutropenia in 308 early‐stage breast cancer patients receiving myelosuppressive chemotherapy. The two treatments were found to be therapeutically equivalent and comparable regarding efficacy and safety.